Comparing the impact of “The Daily Mile™” vs. a modified version on Irish primary school children's engagement and enjoyment in structured physical activity - Hanna, Luke; Burns, Con; O’Neill, Cian; Bolger, Lisa E.; Coughlan, Edward (Frontiers in Sports and Active Living, 2025)
IntroductionThe repetitive nature of The Daily Mile may affect long-term engagement. This study compared the impact of The Daily Mile with a modified version on engagement and enjoyment of structured physical activity.MethodsA ∼7-year-old and ∼11-year old cohort from six primary schools participated in this study, which primarily evaluated pre- to post-assessment changes within each group. Two schools were assigned to The Daily Mile (n = 102 children; M = 8.81 years, SD = 1.97), two schools to the modified version (n = 87; M = 9.16 years, SD = 2.76), and two schools served as controls (n = 79; M = 10.05 years, SD = 1.9) for 10-weeks. Health assessments conducted included cardiorespiratory fitness (550 m Run), fundamental movement skills (Test of Gross Motor Development-2), and health-related quality of life (KIDSCREEN-27). Accelerometers measured school-based physical activity, while enjoyment was assessed using a modified PACES questionnaire. Post-intervention focus groups (n = 10) included teachers and children.ResultsBoth the Daily Mile (∼7-year-old: p < 0.001; ∼11-year-old: p = 0.004) and its modified version (∼7-year-old: p < 0.001; ∼11-year-old: p < 0.001) had a significant impact on cardiorespiratory fitness. Participation in the modified version led to significant improvements in fundamental movement skills (∼7-year-old: p = 0.034; ∼11-year-old: p < 0.001), unlike participation in The Daily Mile (∼7-year-old: p = 1.000; ∼11-year-old: p = 0.807). A significant positive effect on health-related quality of life was attributed to participation in the modified version (p = 0.036), but not to The Daily Mile (p = 0.205). Enjoyment scores were significantly higher for the modified version (4.61 vs. 4.43; p = 0.024).DiscussionParticipation in The Daily Mile is associated with improved health outcomes. Nevertheless, modifying the initiative to include greater variety has the potential to offer broader health benefits, longer engagement, and increased enjoyment. Future research should explore the long-term implementation of this modified version in schools.